Communication strategies and media discourses in the age of COVID-19: an urgent need for action. (9th December 2020) - Généreux, Mélissa; David, Marc D; O'Sullivan, Tracey; Carignan, Marie-Ève; Blouin-Genest, Gabriel; Champagne-Poirier, Olivier; Champagne, Éric; Burlone, Nathalie; Qadar, Zeeshan; Herbosa, Teodoro; Hung, Kevin; Ribeiro-Alves, Gleisse; et al.
Summary: Identified in December 2019 in China, the coronavirus 2019 (COVID-19) has been declared a Public Health Emergency of International Concern (PHEIC). Pandemics share features that increase fear. While some fear can stimulate preventive health behaviors, extreme fear can lead to adverse psychological and behavioral response. The media play a major role shaping these responses. When dealing with a PHEIC, the authorities' communication strategies are embedded in a multilevel governance and a highly hierarchal system, which adds another layer of complexity. Carrying out more 'real-world research' is crucial to generate evidence relating to the psychosocial and behavioral aspects involved during the COVID-19 pandemic and how it is shaped by authorities and media discourses. Interdisciplinary research and international collaborations could contribute to improve our understanding and management of risk information. Emerging from a socio-ecological perspective, future research must integrate multilevel analytical elements, to ensure triangulation of evidence and co-constructing robust recommendations. A mixed-method approach should be privileged to address these issues. At the micro-level, a population-based survey could be conducted in various jurisdictions to assess and compare psychosocial issues according to sociocultural groups. Then, a quantitative/qualitative discourse analysis of the media could be performed. Finally, a network analysis could allow assessing how official information flows and circulates across levels of governance. The COVID-19 represents an opportunity to evaluate the impacts of information/communication strategy and misinformation on various cultural and socioeconomic groups, providing important lessons that could be applied to future health emergencies and disasters.